The Relationship Between E-Hailing Service Quality and User Satisfaction Among Johor, Malaysia - Chen, De Lun; Shafi, Muhammad Ammar (Research in Management of Technology and Business, 2025)
E-hailing services which provide accessibility and convenience have grown to be a major form of transportation in Johor, Malaysia. However, there are gaps in knowledge of how e-hailing service quality and user satisfaction relate to one another, particularly when it comes to aspects like comfort, price, safety, and accessibility. In addition to analysing the relationship between e-hailing service quality and user satisfaction in Johor, this study attempts to determine the elements that affect user satisfaction. Structured questionnaires were used to gather quantitative data from 384 respondents, and SPSS was used for descriptive statistics, reliability, and correlation analysis. According to the findings, price has a minor effect on user satisfaction, but comfort, safety, and accessibility all considerably affect to user satisfaction. Additionally, the quality of e-hailing services and overall user satisfaction are strongly correlated by according to the results. The study suggests more research into other aspects including technology innovation and environmental effect and highlights the significance of ongoing service quality improvement to raise users satisfaction. To give a more comprehensive picture of the dynamics of e-hailing services, future studies should also look at demographic and geographical differences.